Teaching and learning process of test-taking strategies in answering reading comprehension section - Zulmaini, Elika Aji (ELT Forum: Journal of English Language Teaching, 2021)
The study was aimed at finding the difficulties faced by test takers in Reading Comprehension section of TOEFL and describing the teaching and learning process of test-taking strategies of Reading Comprehension section of TOEFL. This study used qualitative research design. To collect the data, the researchers used document analysis and observation as the instrument of the study. The subjects of this study were the students or test takers and a teacher or tutor in TOEFL preparation class. The study showed the range of difficulty faced by students or test takers are skill 6 (57.14%), skill 8 (50%), skill 7, 9, 10, and 11 (33.3%), skill 3 (31%), skill 4 and 12 (16.7%), skill 1 (8.3%), and skill 5 (0%). In teaching and learning strategies, the Planning Strategy was applied in skills 1, 3, 9, 6, 7, 4, 5, and 8. Monitoring Strategies was applied in in skills 1, 3, 9, 6, and 4. Comprehending strategy was used in skills 1, 3, 6, 7, 4, 10, and 11. Retrieval Strategy was applied in skills 9, 5, and 8. Socioaffective strategy was applied in skill 9. Test-wiseness strategy was applied in skills 1, 3, and 9. Based on findings, the researchers found that there is still high percentage of difficult skills faced by students or test takers and more than one strategies were applied in almost every skill of the Reading Comprehension Section of TOEFL.